Custom and path dependence in economics - Rizzello, Salvatore (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2022)
This paper deals with the role of customs in economics. With few exceptions, economists reserved scarce interest to this topic. Some classical authors counterposed custom to market competition, by considering the former as limiting development and the latter as progressing it. By following cognitive economics and particularly Schlicht’s idea that custom derives from a predisposition of human mind to clarity, this paper avoids that dichotomy by investigating the real relationship between them and its relevant implications for economics. In this framework, path-dependence emerges as a unifying element which permeates the indissoluble and complex process and, starting from the construction of personal knowledge, reaches the social dimension of customs. This leads to meaningful perspectives for economic analysis, especially in reference to uncertainty, free will, and efficacy. On a methodological level, the idea of ​​a complete return of economics to social sciences is also supported.